Potential Dust Induced Changes on the Seasonal Variability of Temperature Extremes Over the Sahel: A Regional Climate Modeling Study - Diba, Ibrahima; Basse, Jules; Ndiaye, Mamadou; Sabaly, Hamady Ngansou; Diedhiou, Arona; Camara, Moctar (Frontiers in Earth Science, 2021)
The aim of this study is to simulate the impact of mineral dust emissions from the Sahel-Saharan zone on temperature extremes over the Sahel. To achieve this goal, we performed two numerical simulations: one with the standard version of the regional climate model RegCM4 (no dust run) and another one with the same version of this model incorporating a dust module (dust run). The difference between both versions of the model allowed to isolate the impacts of mineral dust emissions on temperature extremes. The results show that the accumulation of mineral dust into the atmosphere leads to a decrease of the frequency of warm days, very warm days and warm nights over the Sahel. This decrease is higher during the MAM (March-April-May) and JJA (June-July-August) periods especially in the northern and western parts of the Sahel. The impact of the mineral dust emissions is also manifested by a decrease of the frequency of tropical nights especially during MAM in the northern Sahel. When considering the warm spells, mineral particles tend to weaken them especially in MAM and JJA in the northern Sahel. To estimate the potential impacts of the mineral dust accumulation on heat stress, the heat index and the humidex are used. The analysis of the heat index shows that the dust impact is to reduce the health risks particularly in the northern Sahel during the MAM period, in the western Sahel during JJA and in the southern and the north-eastern parts of the Sahel during the SON (September-October-November) period. As for the humidex, it is characterized by a decrease especially in the northern Sahel for all seasons. This work shows that the accumulation of mineral dust particles into the atmosphere may impact positively the human health especially in the northern and western parts of the Sahel by reducing the occurrence of thermal extremes.